Comparative Analysis of Efficacy and Haemodynamic Response between Intrathecal Hyperbaric 0.5% Bupivacaine with Isobaric 0.75% Ropivacaine Utilizing Fentanyl as Adjuvant in Subjects Undergoing Umbilical Surgeries - Anilkumar S Patel; Ambaram Virchanddas Patel (Academia Anesthesiologica International, 2022)
Background: The present study aims the evaluation of hemodynamic reaction and efficiency of Intrathecal hyperbaric 0.5% Bupivacaine with isobaric 0.75% Ropivacaine utilizing Fentanyl in subjects who were planned for infra umbilical surgeries. Subjects and Methods: The patients planned with orthopaedic, urological, gyanecological and general surgeries that involve the lower abdominal area. All the patients were planned under spinal anesthesia. A total of 50 patients were included in the study. Patients were divided into two equal groups. All the patients were included in one of the 2 underneath declared groups as Bupivacaine group (Group B) n=25 and Ropivacaine group (Group R) n=25. Bromage scale was used to evaluate the revial of motor blockage and compactness. To check the loss of sensation the pin prick was utilized. Results: In group B that is Bupivacaine the sensory block was found to be elevated as compared to group R. the dissimilarity was establish to be statistical important. The motor block of 3 mins and hypotension was found to be more advanced and dense in group B as compared to group R patients. Conclusion: As compared to 0.5% bupivacaine; the 0.75% isobaric ropivacaine showed a comparable time of motor blockade. It shows more promising resul with dense motor block with the adjuvant utilization of Fentanyl in both the groups.